Specifics of corporate health programs for railway workers - E. A. Zhidkova; K. G. Gurevich; A. V. Kontsevaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Preventive workplace programs are one of the optimal organizational models for the prevention of noncommunicable diseases in the workingage population. Corporate health programs allow to effectively influence the lifestyle of employees, which makes it possible to reduce human resource risks due to morbidity and increase labor efficiency. First, programs for the prevention of cardiovascular diseases are being implemented. A number of researchers report that implementing prevention programs in the workplace can reduce the number of people with bad habits. The effectiveness of preventive workplace programs largely depends on the mechanisms of their implementation. A feature of railway companies is the presence of a large staff of employees of various specialties. Many factors affecting health are, in one way or another, related to the workflow, since most railway companies operate continuously. Low health literacy of railway workers on health protection and disease prevention was noted. Measures such as financial incentives, preventive counseling, the creation of personalized health profiles and the availability of healthy food in the workplace have been shown to be effective. The review also discusses Russian corporate preventive workplace programs.